2014
DOI: 10.1111/cns.12331
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation ofBDNF‐TrkB Signaling Cascades in Human Hypothalamic Hamartoma (HH): A Potential Mechanism Contributing to Epileptogenesis

Abstract: Our findings suggest that multiple BDNF-TrkB signaling pathways are activated in HH. They act independently or collaboratively to downregulate KCC2 expression, which is the key component for GABA-mediated excitation associated with gelastic seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Paradoxical excitation in response to GABA is likely due to reversal of the intracellular chloride ion gradient associated with the expression profile of NKCC1 and KCC2 (developmentally regulated cation‐chloride transporters within the neuron membrane) . In turn, downregulation of KCC2 expression in HH tissue may be related to hyperactivation of the brain‐derived neurotrophic factor (BDNF)‐trkB signaling pathway …”
Section: Cellular Phenotypesmentioning
confidence: 99%
“…Paradoxical excitation in response to GABA is likely due to reversal of the intracellular chloride ion gradient associated with the expression profile of NKCC1 and KCC2 (developmentally regulated cation‐chloride transporters within the neuron membrane) . In turn, downregulation of KCC2 expression in HH tissue may be related to hyperactivation of the brain‐derived neurotrophic factor (BDNF)‐trkB signaling pathway …”
Section: Cellular Phenotypesmentioning
confidence: 99%
“…Moreover, seizure-related disorders in humans have recently been associated with KCC2 mutations (Kahle et al, 2014; Puskarjov et al, 2014; Stödberg et al, 2015). Deficits in KCC2 expression levels and/or activity also occur in animal models of chronic stress (Hewitt et al, 2009; MacKenzie and Maguire, 2015; Tsukahara et al, 2015, 2016), trauma (Jin et al, 2005), ischemia (Jaenisch et al, 2010), schizophrenia (Hyde et al, 2011) and in peritumoral regions in human brain (Pallud et al, 2014; Semaan et al, 2015). It remains to be determined if deficits in KCC2 activity and expression directly contribute to these varying pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Semaan et al. reported that multiple brain‐derived norotrophic factor tropomyosin receptor kinase B (BDNF‐TrkB) signaling pathways were activated in HH …”
mentioning
confidence: 99%